The Study of Hypermarket in Thailand: The Influence of Store Environments on Consumer Evaluation - Lertsakdumrongkul, Vorapop (2013)
The growth of retail business in Thailand is increasing significantly, especially hypermarket. The first hypermarket in Thailand was introduced in last two decades, and has enormous influence on both Thai people’s lifestyles and retail store businesses in Thailand. The objective of this study is to investigate consumer behavior of store selection by focusing on alternative evaluation stage in consumer decision-making model. The research examines consumer evaluation of hypermarket in Thailand and the influence by consumers’ familiarity and experience. Also, the impacts of store environment factors on consumer alternative evaluation process are investigated. There are four main store environment factors that are explored in this research including music, service quality, crowding, and store layout. The online questionnaire surveys method was implemented to collect the data. The information from 124 Thai respondents was used for data analysis in the study. The results of the analysis show that familiarity level has significant impact on consumer evaluation process both aspects of number of evaluation criteria and consumer evaluation of each attribute. Furthermore, the statistical analysis find that three store environment factors including music, service quality, and store layout have significant positive influence on consumer evaluation of hypermarket in Thailand. On the other hand, crowding aspect shows no significant relationship with consumer evaluation of hypermarket. Managerial implication, research limitation, and suggestion for further research are also mentioned.